Design and field test of crosswise belt type whole plastic-film ridging-mulching corn seeder on double ridges - Dai, Fei; Guo, Wenjuan; Song, Xuefeng; Shi, Ruijie; Zhao, Wuyun; Zhang, Fengwei (International Journal of Agricultural and Biological Engineering, 2019)
In order to realize seedbed mechanization of whole plastic-film mulching on double ridges and to overcome the difficulty in crosswise belt type soil covering by whole plastic-film, a kind of crosswise belt type whole plastic-film ridging-mulching corn seeder on double ridges was designed in this study. The key components of the sample machine was designed and its working parameters of seedbed soil covering device, crosswise-belt soil covering mechanism and profiling sowing depth adjustment device were determined. After numerical simulation on the film edge and crosswise soil covering by whole plastic-film on double ridges by discrete element method, the velocity and displacement of the oscillating plate, and the variation rule of amount of covered soil with time were explored. Field test results show that, when the advancing velocity of the machine was 0.50 m/s, the qualified rate of soil width covered on film edge of the seedbed reached 96.1%, qualified rate of crosswise soil belt width was 94.5%, qualified rate of soil thickness on seedbed was 95.3%, qualified rate of sowing depth was 89.3%, qualified rate of spacing between crosswise soil belts reached 93.6%, which all met related standards in China and satisfied design requirements, and could realize seedbed mechanization of whole plastic-film mulching on double ridges. Comparison tests on working performances of practical soil covering show a basic consistence with the seedbed soil covering simulation, and verified the effectiveness of the soil covering model built by using discrete element method.Keywords: whole plastic-film on double ridges, crosswise belt soil covering, combined machine, discrete element, numerical simulation, field testDOI: 10.25165/j.ijabe.20191204.4860Citation: Dai F, Guo W J, Song X F, Shi R J, Zhao W Y, Zhang F W. Design and field test of crosswise belt type whole plastic-film ridging-mulching corn seeder on double ridges. Int J Agric & Biol Eng, 2019; 12(4): 88–96.